2011
DOI: 10.1074/jbc.m110.176552
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Paracrine Regulation of the Epithelial Na+ Channel by Purinergic Signaling in Mice Lacking Connexin 30

Abstract: We tested whether ATP release through Connexin 30 (Cx30) is part of a local purinergic regulatory system intrinsic to the aldosterone-sensitive distal nephron (ASDN) important for proper control of sodium excretion; if changes in sodium intake influence ATP release via Cx30; and if this allows a normal ENaC response to changes in systemic sodium levels. In addition, we define the consequences of disrupting ATP regulation of ENaC in Cx30 Blood pressure is under negative feedback control. A key factor setting bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
72
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(81 citation statements)
references
References 27 publications
9
72
0
Order By: Relevance
“…It was claimed that gap junction Cx37 and Cx40 transduce purinergic signals mediating renal autoregulation [364]. In a recent paper, it was shown that ATP release through Cx30 is part of a local regulatory system intrinsic to the aldosterone-sensitive distal nephron important for control of sodium excretion [246]. They showed that loss of paracrine ATP feedback regulation of ENaC to respond to changes in sodium levels contributed to salt-sensitive hypertension in Cx30 −/− mice.…”
Section: Hypertensionmentioning
confidence: 99%
“…It was claimed that gap junction Cx37 and Cx40 transduce purinergic signals mediating renal autoregulation [364]. In a recent paper, it was shown that ATP release through Cx30 is part of a local regulatory system intrinsic to the aldosterone-sensitive distal nephron important for control of sodium excretion [246]. They showed that loss of paracrine ATP feedback regulation of ENaC to respond to changes in sodium levels contributed to salt-sensitive hypertension in Cx30 −/− mice.…”
Section: Hypertensionmentioning
confidence: 99%
“…In another study, increasing Na + intake resulted in enhanced urinary ATP secretion, which was robust in WT mice but modest in Cx30 −/− animals. Conversely, epithelial Na + channel (ENaC) activity was greater in Cx30-deffcient animals, likely reflecting decreased ATP release-promoted P2Y 2 receptor-evoked ENaC inhibition [130].…”
Section: Connexinsmentioning
confidence: 99%
“…Indeed, the distal nephron is challenged daily by variations in tubular fluid NaCl concentration as a direct consequence of dietary salt intake. Urinary ATP levels have been shown to increase with dietary Na + intake (56,57). We propose a paradigm in which β-ICs would sense the increase in NaCl delivery to the distal nephron and in turn release ATP/PGE 2 to decrease Na + absorption by adjacent PCs.…”
Section: Figurementioning
confidence: 99%